The Effect of Leverage, Institutional Ownership, and Gender Diversity on the Financial Performance of Manufacturing Companies in Indonesia 2022-2024 Period - Faiz Kanz Pradana; Hardiyanto Wibowo; Iwan Fakhruddin; Tiara Pandansari (Transpublika Publisher, 2026)
Financial performance constitutes a fundamental metric for appraising a firm’s value-generation capabilities and operational sustainability, while simultaneously functioning as a key informational signal for investor assessments of corporate prospects. Internal organizational factors namely leverage, institutional ownership, and board gender diversity are hypothesized to exert influence over this performance. To evaluate these propositions, an associative quantitative methodology utilizing secondary data is applied to manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Through purposive sampling, 90 observations are selected and subjected to multiple linear regression analysis. The resulting findings indicate that, against some expectations, leverage and institutional ownership do not have a significant impact on financial performance within the examined manufacturing firms. By contrast, gender diversity shows a positive and significant effect. These findings provide important implications for company management and stakeholders in designing more inclusive governance strategies, particularly by encouraging increased gender diversity in leadership structures. In addition, the results of this study can serve as a basis for consideration by investors in assessing company performance, as well as for regulators in formulating policies that support sustainable corporate governance practices oriented toward performance improvement.